Cassidinae (Coleoptera: Chrysomelidae) types deposited at Sun Yat-sen University, Guangzhou, China - Sekerka, Lukáš; Jia, Fenglong; Pang, Hong; Borowiec, Lech (Zootaxa, 2016)
Type specimens of Cassidinae deposited at Sun Yat-sen University, Guangzhou, China were studied and as a result following new synonymies are proposed: Cassida expansa Gressitt, 1952 = C. smaragdocruciata Medvedev & Eroshkina, 1982 syn. nov.; C. concha Solsky, 1872 = C. juglans Gressitt, 1942 syn. nov.; Rhoptrispa dilaticotnis (Duvivier, 1891) = Rhadinosa abnormis Gressitt & Kimoto, 1963 syn. nov. Lasiochila fukiena Gressitt, 1950 stat. nov. is removed from synonymy of L. insulana Uhmann, 1929. Each taxon is provided with photograph of dorsal habitus and additional comment clarifiyng its status where necessary.